Kemampuan Berpikir Kritis Siswa Sekolah Dasar pada Pembelajaran IPAS melalui Model PBL Berbantuan Media Question Card - Karina Rosanti; Rohana Rohana; Hendri Gunawan (Lembaga Bale Literasi, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Question Card media on students' critical thinking skills in the IPAS subject on the topic of Human Digestive Organs in Grade V at SD Negeri 123 Palembang for the 2024/2025 academic year. The research employed a quantitative approach using a Posttest-Only Control Group Design. The population consisted of 137 fifth-grade students, and the sampling technique used was Simple Random Sampling, resulting in class V.C as the experimental group and class V.D as the control group, with a total of 67 students. The instrument used was a critical thinking test consisting of 10 essay questions, which had been validated for reliability, difficulty level, and discriminating power. Hypothesis testing was conducted using an Independent Sample t-Test after the data met the requirements for normality and homogeneity. The results showed that the average critical thinking score in the experimental class was 81.73 (very good), while the control class scored 70.37 (good). The t-test results showed that the t value (3.362) was greater than the t table (2.001) at a significance level of 0.05, indicating that Ha was accepted and Ho rejected. Thus, it can be concluded that the Problem Based Learning model assisted by Question Card media has a significant effect on students’ critical thinking skills in IPAS learning.